Microdialysis as a tool for antibiotic assessment in patients with diabetic foot: a review - Fejfarová, Vladimíra; Jarošíková, Radka; Polák, Jan; Sommerová, Blanka; Husáková, Jitka; Wosková, Veronika; Dubský, Michal; Tůma, Petr (Frontiers in Endocrinology, 2023)
Diabetic foot is a serious late complication frequently caused by infection and ischaemia. Both require prompt and aggressive treatment to avoid lower limb amputation. The effectiveness of peripheral arterial disease therapy can be easily verified using triplex ultrasound, ankle-brachial/toe-brachial index examination, or transcutaneous oxygen pressure. However, the success of infection treatment is difficult to establish in patients with diabetic foot. Intravenous systemic antibiotics are recommended for the treatment of infectious complications in patients with moderate or serious stages of infection. Antibiotic therapy should be initiated promptly and aggressively to achieve sufficient serum and peripheral antibiotic concentrations. Antibiotic serum levels are easily evaluated by pharmacokinetic assessment. However, antibiotic concentrations in peripheral tissues, especially in diabetic foot, are not routinely detectable. This minireview describes various microdialysis techniques that have shown promise in determining antibiotic levels in the surroundings of diabetic foot lesions.